The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1080/09540120047440
|View full text |Cite
|
Sign up to set email alerts
|

Preventing HIV infection through peer education and condom promotion among truck drivers and their sexual partners in Tanzania, 1990-1993

Abstract: HIV prevention through peer education and condom promotion among truck drivers and their sexual partners is described. Trends during an initial 18-month intensive phase, followed by a 24-month maintenance phase, were monitored with surveys. Trends for self-reported condom use were: increase among men (56 to 74%) during the first phase with a decrease (72%) during the maintenance phase. Respective figures for women were 51%, 91% and 70%. Multivariate analyses revealed that men most likely to report using condom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
45
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 8 publications
8
45
0
Order By: Relevance
“…Even if women have access to womancontrolled, covert methods of protection, discussion of contraceptive use with the primary male partner is likely (Biddlecom & Fapohunda, 1998;Castle et al, 1999;Green et al, 2001). Thus, it is widely believed that male involvement in family planning is necessary for improved contraceptive use (Sternberg & Hubley, 2004), and there is evidence that interventions targeting men have improved men's acceptance of contraception, including the use of condoms (Piotrow et al, 1992;Celentano et al, 1998;Laukamm-Josten et al, 2000;Leonard et al, 2000;Sternberg & Hubley, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Even if women have access to womancontrolled, covert methods of protection, discussion of contraceptive use with the primary male partner is likely (Biddlecom & Fapohunda, 1998;Castle et al, 1999;Green et al, 2001). Thus, it is widely believed that male involvement in family planning is necessary for improved contraceptive use (Sternberg & Hubley, 2004), and there is evidence that interventions targeting men have improved men's acceptance of contraception, including the use of condoms (Piotrow et al, 1992;Celentano et al, 1998;Laukamm-Josten et al, 2000;Leonard et al, 2000;Sternberg & Hubley, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Peer education involves the dissemination of health-related information and condoms by members of target groups to their peers. Such programs have been shown to increase condom use and reduce levels of HIV and other sexually transmitted infections (STIs) in some countries and contexts in central and southern Africa (Vaz, Gloyd & Trindade, 1996;Laukamm-Josten, Mwizarubi, Outwater, Mwaijonga, Valadez, Nyamwaya et al, 2000;Wolf, Tawfik & Bond, 2000). Others have had more limited success (Leonard, Ndiaye, Kapadia, Eisen, Diop, Mboup et al, 2000) The approach has also been effective in sexual health promotion amongst young people in certain contexts in the United States (Janz, Zimmerman, Wren, Israel, Freudenberg & Carter, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggested that continuous support to maintain the long-term motivation of peer educators is essential to avoid reductions in effectiveness of peer educational programmes (Laukamm-Josten et al, 2000). The Health Centre of Porto provides an important service for commercial sex workers.…”
Section: Discussionmentioning
confidence: 99%